Moldmade Bowls from Straton’s Tower (Caesarea Maritima) - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2020)
The fragments of Hellenistic moldmade bowls (henceforth MMB) presented and discussed in this paper were retrieved in the 1962 Caesarea excavations, conducted by the Hebrew University of Jerusalem under the direction of Michael Avi-Yonah and Avraham Negev with the participation of E. Jerry Vardaman. The assemblage originates from Area D, a long trench measuring 50 m east-west by 10 m north-south, containing re-depositioned late Hellenistic ceramics stored at the Institute of Archaeology, which were never published.